A new terminal converging adaptive control for 6-degree-of-freedom parallel robotic manipulators with bounded control inputs. (April 2017) - Zhao, Dongya; Spurgeon, Sarah K; Liang, Hao; Li, Shaoyuan; Zhu, Quanmin
In this study, a new terminal converging adaptive control approach with bounded control inputs is developed for the 6-degree-of-freedom parallel robot manipulator. The non-smooth feedback control principle is combined with particular bounded functions to define both the control input and associated adaptive law. The Lyapunov method is used to present a stability analysis in order to prove that the error trajectories are semi-globally asymptotically stable. Numerical simulation results relating to a 6-degree-of-freedom parallel robot are presented to validate the effectiveness of the proposed approach and to compare the performance obtained with other candidate control schemes. It is shown that the proposed scheme achieves more rapid error convergence and exhibits improved robustness while guaranteeing that the control signal remains within known bounds.